Justice Holmes's Philosophy - Sheldon M. Novick (Washington University Law Quarterly, 1992)
In my biography of Justice Holmes it seemed proper to let him have his effects. But explanation also has its part to play, if only below decks; so while Holmes lightly touches the helm, we may now trudge down to the engine room and have a look at the machinery.
Keywords: Jurisprudence; Holmes; Oliver Wendell; 1841-1935